Pengolahan Pestisida Nabati Berbahan Dasar Daun Pepaya Di Desa Bamba Puang, Kecamatan Anggeraja, Kabupaten Enrekang: pengolahan pestisida nabati - Kahar, Andi; Marlia Rianti; Andi Irga Satrawati Taslim; Emmi Azis (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
This community service aims to enhance public knowledge about producing botanical pesticides using natural ingredients such as papaya leaves, lemongrass stems, soursop leaves, and garlic. The implementation method involved socialization and training conducted in Bamba Puang Village, Anggeraja Subdistrict, Enrekang Regency, during the Thematic Community Service Program (KKN) by students of Universitas Muhammadiyah Bone. The activities included presentations on the benefits and preparation methods of botanical pesticides, followed by hands-on practice in making the pesticides. The results showed that participants gained new knowledge and skills in creating eco-friendly pesticides and responded positively to the outreach efforts. Thus, this activity successfully raised public awareness about the importance of using botanical pesticides in agriculture..